Spatial expression pattern of serine proteases in the blood fluke Schistosoma mansoni determined by fluorescence RNA in situ hybridization - Ulrychová, Lenka; Ostašov, Pavel; Chanová, Marta; Mareš, Michael; Horn, Martin; Dvořák, Jan (Parasites & vectors, 2021)
BACKGROUND: The blood flukes of genus Schistosoma are the causative agent of schistosomiasis, a parasitic disease that infects more than 200 million people worldwide. Proteases of schistosomes are involved in critical steps of host-parasite interactions and are promising therapeutic targets. We recently identified and characterized a group of S1 family Schistosoma mansoni serine proteases, including SmSP1 to SmSP5. Expression levels of some SmSPs in S. mansoni are low, and by standard genome sequencing technologies they are marginally detectable at the method threshold levels. Here, we report their spatial gene expression patterns in adult S. mansoni by the high-sensitivity localization assay. METHODOLOGY: Highly sensitive fluorescence in situ RNA hybridization (FISH) was modified and used for the localization of mRNAs encoding individual SmSP proteases (including low-expressed SmSPs) in tissues of adult worms. High sensitivity was obtained due to specifically prepared tissue and probes in combination with the employment of a signal amplification approach. The assay method was validated by detecting the expression patterns of a set of relevant reference genes including SmCB1, SmPOP, SmTSP-2, and Sm29 with localization formerly determined by other techniques. RESULTS: FISH analysis revealed interesting expression patterns of SmSPs distributed in multiple tissues of S. mansoni adults. The expression patterns of individual SmSPs were distinct but in part overlapping and were consistent with existing transcriptome sequencing data. The exception were genes with significantly low expression, which were also localized in tissues where they had not previously been detected by RNA sequencing methods. In general, SmSPs were found in various tissues including reproductive organs, parenchymal cells, esophagus, and the tegumental surface. CONCLUSIONS: The FISH-based assay provided spatial information about the expression of five SmSPs in adult S. mansoni females and males. This highly sensitive method allowed visualization of low-abundantly expressed genes that are below the detection limits of standard in situ hybridization or by RNA sequencing. Thus, this technical approach turned out to be suitable for sensitive localization studies and may also be applicable for other trematodes. The results suggest that SmSPs may play roles in diverse processes of the parasite. Certain SmSPs expressed at the surface may be involved in host-parasite interactions.
Keywords: proteiny červů; exprese genu; Gene Expression; Blood fluke; Male; Fluorescence RNA in situ hybridization; Platyhelminthes; hybridizace in situ fluorescenční; Transcript; mužské pohlaví; stanovení celkové genové exprese; Serine Proteases; serinové proteasy; Serine proteases; Gene Expression Profiling; Helminth Proteins; Animals; RNA; ženské pohlaví; zvířata; In Situ Hybridization, Fluorescence; Female; Schistosoma mansoni; mRNA detection